Enhance Knowledge Communication and Learning: A Surprise Paradox. - Chatelain-Jardon, Ruth; Carmona, Jesus S; Daniel, Jose Luis (Journal of Information Systems and Technology Management, 2018)
Human-computer interface is a pivotal factor that can promote or deter the effectiveness of Web-based knowledge communication. There is abundant research that strain to improve interfaces by considering user needs through usability studies, however, few research considers the incorporation of automatic brain mechanisms in order to improve knowledge communication performance. The objective of this research is not to establish a relationship between the negative stimulus presence and improved knowledge communication, but rather to show that the shape of this function follows the Yerkes–Dodson Law. Partial least squares (PLS) was utilized to analyze the data. Results found in this study support the evidence that surprising negative events enhance knowledge communication effectiveness, but more importantly that the surprise-performance relationship is not a linear function but follows the inverted U shape.